Heat transfer augmentation in a circular tube with winglet vortex generators - Chokphoemphun, Suriya; Pimsarn, Monsak; Thianpong, Chinaruk; Promvonge, Pongjet (My University, 2015)
The article presents the influence of winglet vortex generators (WVGs) placed in the core flow area on thermal performance enhancement of a tube heat exchanger. The experiment was carried out in a uniform wall heat-fluxed tube by varying turbulent airflow for Reynolds number ranging from 5300 to 24000. In the present work, the WVGs with an attack angle of 30° were inserted into the test tube at four different winglet pitch ratios (RP = P/D) and three winglet-width or blockage ratios (RB = e/D). The experimental results at various RP and RB values were evaluated and compared with those for smooth tube and tubes with twisted tape or wire coil. The measurement reveals that the WVGs enhance considerably the heat transfer and friction loss above the plain tube, wire coil and twisted tape. The Nusselt number and friction factor increase with the increment of RB and Re but with the decreasing RP. The average Nusselt numbers for the WVGs with various RB are in the range of 2.03-2.34 times above the plain tube. The thermal performance for the WVGs is found to be much higher than that for the wire coil and twisted tape and is in a range of 1.35-1.59. Also, a numerical investigation is conducted to study the flow structure and heat transfer enhancement mechanisms in the winglet-inserted tube.
Keywords: Friction factor; Nusselt number; Thermal enhancement factor; Vortex generator; Winglet